2019
DOI: 10.1002/elan.201900416
|View full text |Cite
|
Sign up to set email alerts
|

Square‐wave Voltammetry of Two‐step Surface Electrode Mechanisms Coupled with Chemical Reactions – A Theoretical Overview

Abstract: Square‐wave voltammetry (SWV) of so‐called “surface redox reactions” is seen as a simple and efficient tool to quantify large number of drugs, physiologically active substances and other important chemicals. It also provides elegant methods to get access to relevant kinetic and thermodynamic parameters related to many lipophilic compounds. Moreover, with this technique we can study activity of various enzymes by exploring the “protein‐film voltammetry” set up. In this work, we focus on theoretical SWV features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…As no redox peak was found in the red and blue lines, it was confirmed that molybdophosphate forms redox currents due to the electron transfer of Mo. In addition, its redox activity was confirmed by square wave voltammetry (SWV) [ 67 , 68 ]. A sample without CRP and a sample with CRP were compared using the fabricated electrochemical immunosensor.…”
Section: Electrochemical Biosensormentioning
confidence: 99%
“…As no redox peak was found in the red and blue lines, it was confirmed that molybdophosphate forms redox currents due to the electron transfer of Mo. In addition, its redox activity was confirmed by square wave voltammetry (SWV) [ 67 , 68 ]. A sample without CRP and a sample with CRP were compared using the fabricated electrochemical immunosensor.…”
Section: Electrochemical Biosensormentioning
confidence: 99%
“…Since many of these enzymes can undergo electrochemical transformation via successive exchange of electrons with the working electrode, their voltammetric patterns can be exceptionally complex [1][2][3][4][5]. As it is described in [11], their complex electrochemistry can be successfully resolved by square-wave voltammetry (SWV). In the theoretical models related to the two-step successive electrode mechanisms of [11][12][13][14][15][16][17][18][19][20], it has been recently reported on reliable procedures to characterize particular electrode enzymatic mechanism, in which coupled chemical steps occur.…”
Section: Introductionmentioning
confidence: 99%
“…As it is described in [11], their complex electrochemistry can be successfully resolved by square-wave voltammetry (SWV). In the theoretical models related to the two-step successive electrode mechanisms of [11][12][13][14][15][16][17][18][19][20], it has been recently reported on reliable procedures to characterize particular electrode enzymatic mechanism, in which coupled chemical steps occur. Moreover, relatively simple methodology has been elaborated…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations